Identification of drought tolerant maize genotypes and seedling based morpho-physiological selection indices for crop improvement - Wattoo, Fahad Masoud; Mehmood Rana, Rashid; Fiaz, Sajid; Zafar, Syed Adeel; Noor, Mehmood Ali; Hassan, Hafiz Mumtaz; Bhatti, Muhammad Husnain; ur Rehman, Shoaib; Anis, Galal Bakr; Muhammad Amir, Rai (Penerbit Universiti Kebangsaan Malaysia, 2018)
Maize is an imperative grain crop used as a staple food in several countries around the world. Water deficiency is a serious problem limiting its growing area and production. Identification of drought tolerant maize germplasm is comparatively easy and sustainable approach to combat this issue. Present research was conducted to evaluate 50 maize genotypes for drought tolerance at early growth stage. Drought tolerance was assessed on the basis of several morphological and physiological parameters. Analysis of variance showed significant variation among the tested maize genotypes for recorded parameters. Principal component analysis revealed important morpho-physiological traits that were playing key role in drought tolerance. Correlation studies depicted significant positive correlation among the attributes such as fresh shoot length (FSL), fresh root length (FRL), dry shoot weight (DSW), dry root weight (DRW), relative water contents (RWC) and total dry matter (TDM) while a strongly negative correlation was observed among RWC and excised leaf water loss. Results concluded that the parameters fresh shoot weight, fresh root weight, FRL, DRW, TDM, cell membrane thermo stability (CMT) and RWC can be useful for rapid screening of maize germplasm for drought tolerance at early growth stages. Furthermore, the genotypes 6, 16, 18, 40, 45 and 50 can be used as a drought tolerant check in breeding programs. Moreover, biplot analysis along with other indices was proved to be a useful approach for rapid and cost efficient screening of large number of genotypes against drought stress condition.